Effects of vitamin D group steroids on mesomorphic phase states of cholesteric sensor materials - Panikarskaya, V.D.; Kasyan, N.A.; Lisetski, L.N.; Terenetskaya, I.P. (Functional Materials, 2005)
Effects of non-mesogenic provitamin D and vitamin D upon thermal stability of cholesteric and smectic-A phases formed by mixtures of cholesterol esters have been studied. Widening of DSC and selective reflection peaks were noted for higher (>5 %) concentrations of provitamin D, which were accompanied by deviations from linearity of concentration dependences of cholesteric - isotropic and cholesteric - smectic transition temperatures. The respective limiting concentrations for provitamins D₂ and D₃ in different matrices correlate with eutectic concentration values calculated using Schroeder-van Laar equations. The results obtained present a physico-chemical basis for development of optimized sensor materials for bioequivalent UV detectors that would meet contradictory requirements of high sensitivity and high thermodynamic stability. Дослiджено вплив немезогенних провiтамiну D та вiтамiну D на термостабiльнiсть холестеричної та смектичної-А фаз, утворених сумiшами естерiв холестерину. Вiдзначено розмиття пiкiв диференцiальної скануючої калориметрiї та селективного вiдбивання для пiдвищених (>5 %) концентрацiй провiтамiну D, яке супроводжується вiдхиленнями вiд лiнiйностi концентрацiйних залежностей температур переходiв холестерик - iзотропна рiдина та холестерик - смектик. Вiдповiднi граничнi концентрацiї для провiтамiнiв D₂ та D₃ у рiзних матрицях корелюють зi значеннями евтектичних концентрацiй, розрахованих за рiвняннями Шредера-ван Лаара. Отриманi результати можуть бути фiзико-хiмiчним пiдгрунтям для розробки сенсорних матерiалiв для бiоеквiвалентних детекторiв УФ-випромiнювання, якi б поєднували високу чутливiсть та термодинамiчну стабiльнiсть. Исследовано влияние немезогенных провитамина D и витамина D на термостабильность холестерической и смектической-А фаз, образованных смесями эфиров холестерина. Отмечено размытие пиков дифференциальной сканирующей калориметрии и селективного отражения для повышенных (>5 %) концентраций провитамина D, сопровождающееся отклонениями от линейности концентрационных зависимостей температур переходов холестерик - изотропная жидкость и холестерик - смектик. Соответствующие граничные концентрации для провитаминов D₂ и D₃ в различных матрицах коррелируют со значениями эвтектических концентраций, рассчитанных по уравнениям Шредера-ван Лаара. Полученные результаты могут быть физико-химической основой для разработки сенсорных материалов для биоэквивалентных детекторов УФ излучения, которые сочетали бы высокую чувствительность и термодинамическую стабильность.